IN ISAJON SULTAN'S NOVEL "BILGA KHAGAN," HISTORICAL REALITY AND ARTISTIC INTERPRETATION COEXIST (Academia Science Repository, 2023)
This page discusses the work "Bilga Khagan" by Uzbekistan's national writer Isajon Sultan, as well as the production, artistry, visuals, and symbolism of the novel "Bilga Khagan."